Kinematika in dinamika: učbenik - Vesenjak, Matej; Kegl, Marko (University of Maribor Press, 2017)
Kinematics and Dynamics. učbenik. The textbook was introduced as didactic support for the subject Kinematics and dynamics at the Faculty of Mechanical Engineering, University of Maribor. A basic level of knowledge in the field of statics and mathematics is expected to comprehend the book of solved problems and exercises.